Slip Flow of MHD Casson Fluid Past a Stretching Sheet with Non-Uniform Heat Source and Sink Effects - et al., Mahantesh M. Nandeppanavar (International Journal of Advanced Science and Technology, 2019)
The present study investigates the slip effects on the flow and heat transfer characteristics ofa non-Newtonian Casson fluid due to the linearly stretching sheet under the influence ofexternal magnetic field. The effects of viscous dissipation and non-uniform heat source/sinkon the heat transfer characteristics of casson fluid are analysed. Suitable similaritytransformations are used to convert the governing non-linear partial differential equations ofmomentum and heat transfer into non-linear ordinary differential equations and then solvednumerically by using Runge-Kutta integration scheme of fourth order along with the shootingtechnique. The heat transfer analysis is made for two different cases of boundary heatingconditions, namely constant surface temperature (CST case) and prescribed surfacetemperature (PST case). The influence of governing non-dimensional parameters on flow andheat transfer characteristics are discussed graphically. It is found from the present analysisthat, the increasing Casson fluid parameter upsurges the temperature field. Also, enhancingmagnetic field decreases the velocity of the fluid. Finally, the present numerical solutions arevalidated with the previously published results and found to be in good agreement